The Graphological ,Typographical and Orthographical Devices in the poetry of e e Cummings (Journal of the College of Basic Education, 2022)
Critics were not always on the American poet Edward Estlin Cummings’ side and mostly he was a target to their invective criticism .The reason is that the style of this poet is inventive and eccentric to such an extent that it makes his poems difficult for the reader unfamiliar with his style. The invented a new style by which he transforms the traditional language to a means to express his feelings and ideas into a visual art . He works with great freedom on the shapes and sizes of letters and their distribution on page , the words and their syntactic function and also on grammatical rules and punctuation to make the influence he desires . There is a strong connection between form and content in the poetry of Cummings. The poet draws with words and letters to present a visual image and this makes it impossible to read his poetry aloud .